Inhibitors of Serine/Threonine Protein Phosphatases: Biochemical and Structural Studies Provide Insight for Further Development - Swingle, Mark R.; Honkanen, Richard E. (Current Medicinal Chemistry, 2019)
Background: The reversible phosphorylation of proteins regulates many key functions in eukaryotic cells. Phosphorylation is catalyzed by protein kinases, with the majority of phosphorylation occurring on side chains of serine and threonine residues. The phosphomonoesters generated by protein kinases are hydrolyzed by protein phosphatases. In the absence of a phosphatase, the half-time for the hydrolysis of alkyl phosphate dianions at 25º C is over 1 trillion years; knon 2 x 10-20 sec-1. Therefore, ser/thr phosphatases are critical for processes controlled by reversible phosphorylation. Methods: This review is based on the literature searched in available databases. We compare the catalytic mechanism of PPP-family phosphatases (PPPases) and the interactions of inhibitors that target these enzymes. Results: PPPases are metal-dependent hydrolases that enhance the rate of hydrolysis ([kcat/kM]/knon ) by a factor of 1021, placing them among the most powerful known catalysts on earth. Biochemical and structural studies indicate that the remarkable catalytic proficiencies of PPPases are achieved by 10 conserved amino acids, DXH(X) 26DXXDR(X) 20- 26NH(X) 50H(X) 25-45R(X) 30-40H. Six act as metal-coordinating residues. Four position and orient the substrate phosphate. Together, two metal ions and the 10 catalytic residues position the phosphoryl group and an activated bridging water/hydroxide nucleophile for an inline attack upon the substrate phosphorous atom. The PPPases are conserved among species, and many structurally diverse natural toxins co-evolved to target these enzymes. Conclusion: Although the catalytic site is conserved, opportunities for the development of selective inhibitors of this important group of metalloenzymes exist.
Keywords: microcystin crystal structures